Retinoblastoma in an older child: A case report - Zhuan, Ong Wu; Rahmat, Jamalia; Ramasamy, Sunder; Samsudin, Amir (Universiti Putra Malaysia, 2018)
Retinoblastoma is a rare intraocular malignant tumour more commonly seen in children below five years of age. We presented a rare case of retinoblastoma in an older child. A nine-year-old girl noticed that she had loss of vision OS following a fall at home. Her vision was 6/6 OD and only light perception OS. Examination of the left eye revealed an extensive exudative retinal detachment. Her right eye examination was unremarkable. CT scan showed a left eye intraocular mass with calcification. EUA revealed a mixed endophytic and exophytic mass with extensive exudative retinal detachment. Family members consented to left eye enucleation and histopathological report confirmed the diagnosis of retinoblastoma. Post enucleation, patient is doing well with a prosthetic eye. In conclusion, any unexplained visual loss in children regardless of age warrants a full ophthalmological examination as the possibility of retinoblastoma cannot be ruled out.